Embodiment of The Principle of Opportunity Through The Authority of Deponering by The Attorney General in Criminal Justice in Indonesia - I Putu Gede Titan Bismantara; I Dewa Gede Dana Sugama (Fakultas Hukum, Universitas Warmadewa, 2025)
This study aims to provide an explanation regarding the authority of the Attorney General in deponeering a case, which is an important aspect of the Indonesian criminal justice system. It relates to prosecutorial policies that can influence the course of legal proceedings and the legal consequences arising from the deponering provisions outlined in the Prosecutor's Office Law. Deponering, in simple terms, refers to the cessation of prosecution of an ongoing case, granted to the Attorney General with the aim of considering the broader public interest and the utility of the ewalaw. However, the existing regulations still provide ambiguous provisions regarding the authority of deponering. For example, Law Number 11 of 2021 does not clearly outline the criteria for cases that can be classified as involving